Is it more effective for highly trained swimmers to live and train at 1200 m than at 1850 m in terms of performance and haematological benefits?. Issue 2 (23rd January 2006) - Roels, B; Hellard, P; Schmitt, L; Robach, P; Richalet, J-P; Millet, G P
Abstract : Objectives: The effects of living and training have not been compared at different altitudes in well trained subjects. Methods: Nine international swimmers lived and trained for 13 days similarly at 1200 m (T1200) and 1850 m (T1850). The two altitude training periods were separated by six weeks of sea level training. Before and after each training trip, subjects performed, at an altitude of 1200 m, an incremental exercise test to exhaustion of 5 × 200 m swims and a maximal test over 2000 m. Results: There was no difference in V˙o 2 max after each training trip: the before values were 58.5 (5.6) and 60.4 (6.7) ml/kg/min and the after values were 56.2 (5.2) and 57.1 (4.7) ml/kg/min for T1200 and T1850 respectively. The 2000 m performance had improved during T1200 (1476 (34) to 1448 (45) seconds) but not during T1850 (1458 (35) v 1450 (33) seconds). Mean cell volume increased during T1850 (86.6 (2.8) to 88.7 (2.9) µm 3 ) but did not change during T1200 (85.6 (2.9) v 85.7 (2.9) µm 3 ). The proportion of reticulocytes decreased during T1200 (15.2 (3.8)% to 10.3 (3.4)%) and increased during T1850 (9.3 (1.6)% to 11.9 (3.5)%). Conclusions: The short term effects of 13 days of training at 1200 m on swimming performance appear to be greater than the same type of training for the same length of time at 1850 m. As mean cell volume and proportion of reticulocytes only increased during training at 1850 m, the benefits of training at this altitude may be delayed and appear later on.